1998
DOI: 10.1007/s004380050919
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of a histone-like protein in dormant Mycobacterium smegmatis

Abstract: The aerobic saprophyte Mycobacterium smegmatis, like its pathogenic counterpart M. tuberculosis, has the ability to adapt to anaerobiosis by shifting down to a dormant state. Here, we report the identification and molecular genetic characterisation of the first dormancy-induced protein in M. smegmatis. Comparative SDS-polyacrylamide gel electrophoresis of protein extracts of aerobically growing and dormant anaerobic M. smegmatis cultures revealed the upregulation of a 27-kDa protein in the dormant state. Pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
73
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 22 publications
3
73
0
Order By: Relevance
“…Under these conditions, the bacteria shut down protein synthesis, but it restarts immediately after the reintroduction of oxygen (Hu et al, 1998). Similar quiescent non-replicating states have recently been described for Mycobacterium smegmatis (Lee et al, 1998) and Mycobacterium bovis (Lim et al, 1999). Since none of these bacteria require a period of resuscitation, they should not be considered as dormant .…”
Section: Introductionsupporting
confidence: 55%
“…Under these conditions, the bacteria shut down protein synthesis, but it restarts immediately after the reintroduction of oxygen (Hu et al, 1998). Similar quiescent non-replicating states have recently been described for Mycobacterium smegmatis (Lee et al, 1998) and Mycobacterium bovis (Lim et al, 1999). Since none of these bacteria require a period of resuscitation, they should not be considered as dormant .…”
Section: Introductionsupporting
confidence: 55%
“…Importantly, MDP1 inhibits macromolecular biosyntheses of DNA, RNA, and protein in vitro and recombinant E. coli expressing MDP1 grows much slower when compared to the parental strain (13). The expression of MDP1 is up-regulated at the stationary or dormant phases of mycobacterial culture (11,14). MDP1 and its homologues, which have been designated as histone-like protein (14) and laminin-binding protein (LBP) (15), are distributed in all mycobacterial species so far examined (12).…”
mentioning
confidence: 99%
“…The expression of MDP1 is up-regulated at the stationary or dormant phases of mycobacterial culture (11,14). MDP1 and its homologues, which have been designated as histone-like protein (14) and laminin-binding protein (LBP) (15), are distributed in all mycobacterial species so far examined (12). These imply that MDP1 plays an important role in both slow growth and dormant/latent infection with mycobacteria.…”
mentioning
confidence: 99%
“…The cellular content of MDP1 is increased in the stationary growth phase of mycobacteria relative to the exponential growth phase (14). Dick et al (17) found that histone-like protein (HLP), the homologue of MDP1, was substantially upregulated in the dormant state of Mycobacterium smegmatis. Our previous study showed that MDP1 inhibited macromolecular biosyntheses in vitro and substantially suppressed bacterial growth (18).…”
mentioning
confidence: 99%